1996
DOI: 10.5326/15473317-32-4-287
|View full text |Cite
|
Sign up to set email alerts
|

Gastric dilatation-volvulus in the dog with histological evidence of preexisting inflammatory bowel disease: a retrospective study of 23 cases

Abstract: The gastric dilatation-volvulus (GDV) syndrome in the dog is considered to be multifactorial. The medical records of 42 dogs treated for GDV between 1990 and 1994 were reviewed in an effort to evaluate the correlation between GDV and preexisting gastrointestinal disease. Twenty-three cases fit the inclusion criteria of an intestinal biopsy taken at the time of corrective surgery and a complete medical history. The microscopic jejunal changes expected from the acute vascular compromise in these animals were dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…The aetiology of GDV is not yet known, but many predisposing factors have been described, including decreased gastric motility, inflammatory bowel disease or other signs of impaired gastrointestinal function (Hall et al 1993;Braun et al 1996;Beck et al 2006). Many studies have focused on the identification of endogenous and exogenous factors which may help in the identification of dogs at risk of GDV.…”
Section: Gastric Dilatation and Volvulus Syndrome (Gdv)mentioning
confidence: 99%
“…The aetiology of GDV is not yet known, but many predisposing factors have been described, including decreased gastric motility, inflammatory bowel disease or other signs of impaired gastrointestinal function (Hall et al 1993;Braun et al 1996;Beck et al 2006). Many studies have focused on the identification of endogenous and exogenous factors which may help in the identification of dogs at risk of GDV.…”
Section: Gastric Dilatation and Volvulus Syndrome (Gdv)mentioning
confidence: 99%
“…Underlying GI pathology (eg, IBD or GI lymphoma) was suspected as the cause of persistent gastric distension and dysmotility and empiric therapy improved the cat's clinical signs; acquisition of GI biopsies at the time of surgery may have helped to reach a definitive diagnosis in this case. While there is a report of a possible association between GDV and IBD in dogs, the current evidence is not compelling enough to recommend the acquisition of GI biopsies in all cases of GDV. It would have been ideal if retroviral (feline leukemia and feline immunodeficiency virus) testing had been confirmed in either case to investigate these viruses as a possible cause of gastrointestinal dysmotility in accordance with the most recent American Association of Feline Practitioners recommendations …”
Section: Discussionmentioning
confidence: 87%
“…A retrospective study that evaluated further possible predisposing factors found that 61% of 23 dogs with GDV had pre‐existing gastrointestinal disease (i.e. inflammatory bowel disease), suggesting that underlying medical conditions may influence the risk of developing GDV (Braun et al., 1996).…”
Section: Discussionmentioning
confidence: 99%